Adjuvant Concurrent Chemoradiotherapy Versus Adjuvant Chemotherapy Only in Locally Advanced Non-small-cell Lung Cancer With Involved Microscopic Resection Margin: A Population-based Cohort Study - TU, CHIH-YEN; CHEN, HUNG-JEN; HSIA, TE-CHUN; FANG, HSIN-YUAN; LI, CHIA-CHIN; CHIEN, CHUN-RU (Anticancer research, 2022)
The role of adjuvant concurrent chemoradiotherapy (aCCRT) for locally advanced non-small cell lung cancer (LA-NSCLC) treated with radical surgery, with microscopically involved resection margin, has been debated without there being any direct evidence. In this study, we aimed to compare the outcomes between aCCRT and adjuvant chemotherapy (aCT). Eligible patients diagnosed within 2011-2018 with LA-NSCLC were identified via the Taiwan Cancer Registry. We used propensity-score weighting to balance observable potential confounders, and then compared the hazard ratios of death between aCCRT-treated vs. aCT-treated groups. We also performed supplementary analyses using propensityscore matching. Our main study population consisted of 82 patients. The propensity score weight-adjusted hazard ratio of death for the aCCRT group was 0.74 (95% confidence interval=0.35-1.56, p=0.43). There was also no statistically significant difference in survival between groups in the supplementary analyses. For patients treated with radical but R1 resection for LA-NSCLC, there was no significant OS benefit from the addition of concurrent radiotherapy.